Artificial intelligence in marketing - Malhotra, Naresh K.; Sudhir, K.; Toubia, Olivier (Bingley, U.K. : Emerald Publishing Limited, 2023)
Review of Marketing Research pushes the boundaries of marketing--broadening the marketing concept to make the world a better place. Here, leading scholars explore how marketing is currently shaping, and being shaped by, the evolution of Artificial Intelligence (AI). Topics covered include the effects of AI on: economics; personalisation; pricing; content generation; the identification, structuring, and prioritization of customer needs; customer feedback; Natural Language Processing; image analytics; deep learning; and the anthropomorphism of AI, such as in virtual assistants and chatbots. Each chapter provides thought provoking discussions which will be relevant to researchers, professionals, and students.
Introduction. The state of AI research in marketing: Active, fertile, and ready for explosive growth / K. Sudhir and Olivier Toubia -- Chapter 1. The economics of artificial intelligence: A marketing perspective / MengQi (Annie) Ding and Avi Goldfarb -- Chapter 2. AI and personalization / Omid Rafieian and Hema Yoganarasimhan -- Chapter 3. Artificial intelligence and pricing / Diego Aparicio and Kanishka Misra -- Chapter 4. Leveraging AI for content generation: A customer equity perspective / David Schweidel, Martin Reisenbichler, Thomas Reutterer, and Kunpeng Zhang -- Chapter 5. Artificial intelligence and user-generated data are transforming how firms come to understand customer needs / John R. Hauser, Zelin Li, and Chengfeng Mao -- Chapter 6. AI applications to customer feedback research: A review / Peter S. Lee, Ishita Chakraborty, and Shrabastee Banerjee -- Chapter 7. Natural language processing in marketing / Jochen Hartmann and Oded Netzer -- Chapter 8. Marketing through the machine's eyes: Image analytics and interpretability / Shunyuan Zhang, Flora Feng, and Kannan Srinivasan -- Chapter 9. Deep learning in marketing: A review and research agenda / Xiao Liu -- Chapter 10. Anthropomorphism in artificial intelligence: A review of empirical work across domains and insights for future research / Ertugrul Uysal, Sascha Alavi and Valéry Bezençon.
Includes bibliographical references and index.
Print version record.
Keywords: Artificial intelligence -- Marketing applications; Business & Economics -- Marketing -- General; Sales & marketing